Potential development of an optical sensor to determine the quality of heated palm cooking oil - Wan Shafiq, Salleh; Nurulain Atikah, Shaipuzaman; Suhaila, Mohd Najib; Mohd Rashidi, Salim; Hadi, Manap (Institute of Advanced Engineering and Science, 2022)
Palm oil is an edible vegetable oil yielded from the mesocarp of the palm oil’s fruit. It is commonly used as cooking oil as compared to other cooking oil such as olive or coconut oil because it is inexpensive and has high oxidative stability when used for frying. However, after frequent frying, the oil undergoes some physical and chemical reactions which affect the quality. This leads to the formation of compound that is dangerous to human body which is called free fatty acid (FFA). Therefore, a measurement device needs to be developed to determine the quality of heated cooking oil. In this paper, a spectroscopy study using an open-path method which focus on the palm cooking oil is proposed to examine the reaction of palm oil upon prolonged heating process. Open-path method is a technique where the incident beam will travel through the sample (palm oil) before it is detected by a spectrometer. The result shows that the FFA samples have the optimum absorbance peak at the UV wavelength 339.15 nm and each prolonged heated oil show different absorbance value. Hence, there is a potential to develop an optical sensor to determine the quality of the heated cooking oil.